Enantiomeric blends of high-molecular-weight poly(lactic acid)/poly(ethylene glycol) triblock copolymers: Enhanced stereocomplexation and thermomechanical properties. (26th October 2016) - Han, Lili; Yu, Chengtao; Zhou, Jian; Shan, Guorong; Bao, Yongzhong; Yun, Xueyan; Dong, Tungalag; Pan, Pengju
Abstract: Poly(l -lactic acid)-poly(ethylene glycol)-poly(l -lactic acid) (PLLA-PEG-PLLA) and poly(d -lactic acid)-poly(ethylene glycol)-poly(d -lactic acid) (PDLA-PEG-PDLA) triblock copolymers having relatively high molecular weights ( M n  > 60 kDa) and different lengths of PEG midblock (2–20 kDa) and PLLA, PDLA end blocks (20–45 kDa for each block) were prepared and blended in equal mass. The competing crystallization kinetics, polymorphic crystalline structure, mechanical and thermomechanical properties of PLLA-PEG-PLLA/PDLA-PEG-PDLA blends were investigated and compared with the PLLA/PDLA blend. Both the crystallization rate and stereocomplexation ability of PLLA/PDLA blends were improved after the incorporation of PEG midblocks. The crystallization half-time decreases and the crystallinity, content of stereocomplexes (SCs) enhance as the length of PEG midblock increases or the lengths of PLLA, PDLA end blocks decease. The melt recrystallization from homocrystallites (HCs) to SCs becomes more pronounced with increasing the length of PEG midblocks in the enantiomeric blends. The enhanced SC formation and crystallization rate of PLLA-PEG-PLLA/PDLA-PEG-PDLA blends are attributed to the increased diffusion ability and decreased diffusion pathway of enantiomeric chains. The synergistic effects of stereocomplexation and plasticization of flexible PEG midblocks offer the PLLA-PEG-PLLA/PDLA-PEG-PDLA blended materials better mechanical and thermomechanical properties. The enantiomeric blends exhibit higher tensile strength, larger elongation-at-break, and better thermal resistance than the corresponding PLLA-PEG-PLLA copolymers. Graphical abstract: Highlights: A flexible PEG is found to enhance the stereocomplexation and toughness of high-molecular-weight PLAs. The incorporated PEG can improve the crystallization rate and stereocomplexation ability of PLLA/PDLA blends. Stereocomplexation and plasticization effects offer the enantiomeric blends better mechanical properties.